2019
DOI: 10.1002/pca.2872
|View full text |Cite
|
Sign up to set email alerts
|

New technological approaches for recovering bioactive food constituents from sweet cherry (Prunus avium L.) stems

Abstract: Introduction In recent years, an increasing interest in biological properties of sweet cherry (Prunus avium L.) stems has resulted in increased attention for advanced extraction techniques and their optimisation. Objectives In the present study chemical profiles of P. avium stems extracts obtained by selected emerging technologies, such as pressurised liquid extraction (PLE) and supercritical fluid extraction (SFE), under different experimental conditions were compared. Material and Methods All SFEs were carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…The previous studies about cherry stem reported that it had quercetin, catechin, chlorogenic acid, rutin (Ademović et al, 2017), gallic acid, epicatechin, naringenin, caffeic acid, p‐coumaric acid, vanillic acid, quercetin, and kaempferol and some of their derivatives (Nastić et al, 2020). In another study, caffeic acid (91.3–11.4 mg/kg), ferulic acid (220–231 mg/kg), pyrogallol (261–262 mg/kg), coumaric acid (161 mg/kg), gallic acid (41.1–50.3 mg/kg), ellagic acid (71.1 mg/kg), and quercetin (116 mg/kg) were identified in the water and ethanol extract of the cherry stem (Bursal et al., 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous studies about cherry stem reported that it had quercetin, catechin, chlorogenic acid, rutin (Ademović et al, 2017), gallic acid, epicatechin, naringenin, caffeic acid, p‐coumaric acid, vanillic acid, quercetin, and kaempferol and some of their derivatives (Nastić et al, 2020). In another study, caffeic acid (91.3–11.4 mg/kg), ferulic acid (220–231 mg/kg), pyrogallol (261–262 mg/kg), coumaric acid (161 mg/kg), gallic acid (41.1–50.3 mg/kg), ellagic acid (71.1 mg/kg), and quercetin (116 mg/kg) were identified in the water and ethanol extract of the cherry stem (Bursal et al., 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Up to now, although the cherry fruit phenolics have been widely studied (Aires et al., 2017; Chaovanalikit & Wrolstad, 2004; de Souza et al., 2014), the number of the studies about extraction of the cherry stem phenolics and investigation of their bioactive compounds and their biological activities in detail are limited (Bastos et al., 2015; Bursal, Köksal, Gülçin, Bilsel, & Gören, 2013; Jesus, Gonçalves, Alves, & Silva, 2019; Švarc‐Gajić et al, 2018; Topaloğlu, 2015). The studies about cherry stem reported that it had some volatile compounds (hydrocarbon and oxygenated terpenes) (Piccirillo, Demiray, Ferreira, Pintado, & Castro, 2013), alcohols, fatty acids (Nastić, Lozano‐Sánchez, Borrás‐Linares, Švarc‐Gajić, & Segura‐Carretero, 2020), organic acids (Švarc‐Gajić et al, 2018), different phenolic compounds, and their derivatives (Ademović et al, 2017; Bastos et al., 2015; Bursal et al., 2013; Nastić et al, 2020; Piccirillo et al., 2013; Švarc‐Gajić et al, 2018; Topaloğlu, 2015). However, if the resulting product is going to be used in food or nonfood applications, the extraction process of the phenolic compounds from the cherry stem requires greater attention and detailed studies in point of their yield and biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies used in identifying these compounds were those that evaluated the chemical composition of other species of the genus Cassia, Fabaceae family or specimens of the same C. grandis class [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Figure 1 showed a base peak chromatogram (BPC) representative of the carao seed extracts obtained by HPLC-ESI-TOF-MS in negative polarity.…”
Section: Identification Of Polar Compounds In Ple Extracts Of C Granmentioning
confidence: 99%
“…Finally, the subclass of proanthocyanidins included Peaks 8,12,13,14,21,23,29,31,32,33,34,35, 37 and 39. Peaks 8 and 12 were detected in all extraction conditions.…”
Section: Flavonoidsmentioning
confidence: 99%
See 1 more Smart Citation